How Hydroxyurea Alters the Gut Microbiome: A Longitudinal Study Involving Angolan Children with Sickle Cell Anemia - Delgadinho, Mariana (2022)
Sickle cell anemia (SCA) is an inherited hematological disorder and a serious global health problem, especially in Sub-Saharan Africa. Although hydroxyurea (HU) is the leading treatment for patients with SCA, its effects on the gut microbiome have not yet been explored. In this context, the aim of this study was to investigate this association by characterizing the gut microbiome of an Angolan SCA pediatric population before and after 6 months of HU treatment. A total of 66 stool samples were obtained and sequenced for the 16S rRNA gene (V3-V4 regions). Significant associations were observed in alpha and beta-diversity, with higher values of species richness for the children naïve for HU. We also noticed that children after HU had higher proportions of several beneficial bacteria, mostly short-chain fatty acids (SCFAs) producing species, such as Blautia luti, Roseburia inulinivorans, Eubacterium halli, Faecalibacterium, Ruminococcus, Lactobacillus rogosae, among others. In addition, before HU there was a higher abundance of Clostridium_g24, which includes C. bolteae and C. clostridioforme, both considered pathogenic. This study provides the first evidence of the HU effect on the gut microbiome and unravels several microorganisms that could be considered candidate biomarkers for disease severity and HU efficacy.